EGG WEIGHT AFFECTS HATCHING RESULTS, BODY WEIGHT AND FEAR-RELATED BEHAVIOR IN JAPANESE QUAILS - Magda Ismail Abo-Samaha; Sara Elsayed El-kazaz (Slovenian Veterinary Research, 2020)
This study was conducted to determine effect of egg weight on hatching results, chick performance and tonic immobility duration in Japanese Quails. Eggs were weighed individually and divided by weight into four groups: group 1 = 11.0 - 11.9 g, group 2 = 12.0 - 12.9 g, group 3 = 13.0 - 13.9 g and group 4 = 14.0 - 14.9 g. Egg weight loss during incubation and hatching parameters were recorded. Additionally, hatching weight and body weight were measured until 5 weeks and tonic immobility (TI) test was performed at the end of the experiment. Results revealed that egg weight loss during incubation decreased as egg weight increased. Group 2 was determined as the best suitable egg weight group in terms of fertility and group 2 and 3 in terms of hatchability of incubated eggs and hatchability of fertile eggs. Body weight increased as the egg weight increased and the heaviest chicks were hatched from heaviest egg group.  Significant differences in TI duration between birds were noticed, as higher body weight birds had longer TI duration than birds with lower body weight. Thus, birds of high body weight were more fearful than birds of low body weight. It was concluded that the medium to heavy weight eggs are better eggs for hatching results and chick weight. Therefore, we recommend the selection of medium and heavy weight eggs for hatching implementations in Japanese quail.